2018
DOI: 10.1111/bju.14485
|View full text |Cite
|
Sign up to set email alerts
|

Is postoperative Doppler ultrasonography useful for the early detection of asymptomatic pseudoaneurysm and prevention of haemorrhagic complications after partial nephrectomy?

Abstract: ObjectiveTo assess the clinical utility of systematic Doppler ultrasonography (DUS) after robot-assisted partial nephrectomy (PN) for the detection of renal artery pseudoaneurysm (PA) and to allow pre-emptive arterial embolization to reduce the postoperative bleeding risk. Materials and MethodsA retrospective study was conducted including all consecutive patients treated with robot-assisted PN for renal tumours between 2015 and 2017. Every patient underwent renal DUS in the early postoperative period. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Conversely, routine postoperative CE-CT may carry greater risk of overimaging, overdiagnosis, and overtreatment of asymptomatic RAP, as in our two patients who underwent prophylactic RAE for asymptomatic RAP diagnosed by routine CE-CT 7 days after RAPN. Further, the usefulness of Doppler ultrasonography for the early detection of significant asymptomatic RAP has been reported (30). Against this background, we found that RAPs of 15 mm or less disappear spontaneously after 3 months, suggesting that routine early postoperative imaging including CE-CT is not required in the absence of clinical signs or symptoms such as gross hematuria.…”
Section: Discussionsupporting
confidence: 58%
“…Conversely, routine postoperative CE-CT may carry greater risk of overimaging, overdiagnosis, and overtreatment of asymptomatic RAP, as in our two patients who underwent prophylactic RAE for asymptomatic RAP diagnosed by routine CE-CT 7 days after RAPN. Further, the usefulness of Doppler ultrasonography for the early detection of significant asymptomatic RAP has been reported (30). Against this background, we found that RAPs of 15 mm or less disappear spontaneously after 3 months, suggesting that routine early postoperative imaging including CE-CT is not required in the absence of clinical signs or symptoms such as gross hematuria.…”
Section: Discussionsupporting
confidence: 58%
“…Doppler ultrasonography (DUS), unlike CECT, is a simple, secure, and cost‐effective tool. Nevertheless, its diagnostic ability to identify RAP as a screening test has only been evaluated in a small number of patients 2,3 . Here, we evaluated the diagnostic ability of DUS for the detection of asymptomatic RAP using a relatively large consecutive patient cohort spanning 15 years at a single institution.…”
Section: Figurementioning
confidence: 99%
“…If the patient experiences rapid clinical deterioration or has required blood transfusion of greater than two units, early consideration of angioembolization should be sought for control of potential segmental arterial bleeding (64). Uncommonly, delayed presentation of arteriovenous fistulas and renal artery pseudoaneurysms can present with hematuria, wound site bleeding or flank pain and are potentially life-threatening (69). This may also be managed with embolization (65).…”
Section: Post-operative Issuesmentioning
confidence: 99%